Characteristics of neutron beams from deuterated targets irradiated by intense sub-ps lasers - P. Martin; M. Borghesi; S. Kar (Physical Review Research)
The generation of energetic neutron beams by d(d,n)^{3}He reactions during the interaction of an intense laser with micron-thick deuterated plastic targets is investigated through two-dimensional particle-in-cell simulations equipped with nuclear reaction formalism. The capability of modeling neutron generation along with laser-plasma interaction enables us to identify and quantify multiple distinct and competing regimes of neutron production happening concurrently at the laser irradiated target. The high-energy neutrons are seen to be produced by two different mechanisms of ion acceleration in thick targets, namely, hole boring radiation pressure occurring inside the target bulk and target normal sheath acceleration that occurs on the rear surface of the target. These two regimes contribute two distinctly different components to the final neutron spectrum. Further a narrow-band (2–3 MeV), quasi-isotropic neutron production of significant flux is also seen during the interaction due to shocklike features seeded inside the bulk target plasma by the fast expansion of contaminant species from the target's front and rear surfaces. While the peak neutron energy is found to saturate at high laser intensities, the integrated flux continues to scale favorably.